1986
DOI: 10.1080/00039896.1986.9935784
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Count Suppression without Endocrine Dysfunction in Lead-Exposed Men

Abstract: To determine if increased lead absorption was associated with sperm count suppression or perterbation of the hypothalamopituitary system, we compared battery workers (N = 18), who were exposed to high airborne lead levels, with cement workers (N = 18), who were exposed to ambient lead levels. Blood lead, urinary lead, semen lead, and zinc protoporphyrin concentrations were markedly elevated (p less than .001) in battery workers. Battery workers had a significantly shifted (p less than .025) frequency distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
5

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 12 publications
2
42
1
5
Order By: Relevance
“…Corroboration of these findings is provided by two recent studies, which also observed sperm count depression at relatively high blood lead levels (> 60 jig/dL) (49,50).…”
Section: Reproductive Lbxicity Of Leadmentioning
confidence: 89%
“…Corroboration of these findings is provided by two recent studies, which also observed sperm count depression at relatively high blood lead levels (> 60 jig/dL) (49,50).…”
Section: Reproductive Lbxicity Of Leadmentioning
confidence: 89%
“…Effects on the reproductive endocrine function have been less consistent (71,74,(79)(80)(81)(82)(83). Reduced sperm count and concentration, and lower motility were found in lead workers with blood lead levels lower than 400 µg L -1 (78,(84)(85).…”
Section: Effects Of Occupational Exposure To Metals On Reproductive Pmentioning
confidence: 99%
“…In men occupationally exposed to lead, blood lead levels equal to or higher than 400 µg L -1 have been associated with reduced sperm count, poor semen motility, and abnormal sperm morphology, particularly of the sperm head (69)(70)(71)(72)(73)(74)(75)(76)(77)(78). Effects on the reproductive endocrine function have been less consistent (71,74,(79)(80)(81)(82)(83).…”
Section: Effects Of Occupational Exposure To Metals On Reproductive Pmentioning
confidence: 99%
“…Males employed in metal industries had a decreased fertility when compared with other workers as shown by a delayed pregnancy and reduced semen quality [26,36,45,[63][64][65][66][67][68][69]. Akinloye et al [68] analyzed the serum and seminal plasma concentrations of cadmium (Cd) in 60 infertile males and 40 normozoospermic subjects.…”
Section: Metalsmentioning
confidence: 99%
“…1). Any of those mechanisms would result in poor semen quality [26,36,37]. Recent studies suggest that sperm DNA integrity may be altered by environmental exposure to some toxic chemicals [38,39].…”
Section: Introductionmentioning
confidence: 99%